Revitalizing Islamic Values Education through PAMI: A Community-Based Approach to Fostering Piety and Character for SDG 4 - Salwa Salsabilah; Ahmad Ridwan; Muhammad Bilal Sarfraz (Profetika: Jurnal Studi Islam, 2025)
Objective: This study aims to analyze the implementation and revitalization of the Recitation Between Maghrib and Isha or Pengajian antara Maghrib dan Isya (PAMI) as a mosque-based Islamic education model in shaping the piety character of school-age children and identifying challenges and strategies for its development in the digital era, in support of the SDGs goals in the field of quality education. Theoretical framework: This study uses the concept of character education in Islam, which emphasizes the integration of faith, worship, and morals, as well as a community-based educational approach that places mosques as the center of moral and spiritual development. Literature review:  The literature shows that mosques play an important role as non-formal Islamic educational institutions in the formation of children's character, but face modern challenges such as the influence of digital technology and low participation of the younger generation. Methods: The study used a qualitative approach with ethnographic design through observation, interviews, and documentation at the Riyadhul Abidin Mosque, Jambi City, with data analysis of Miles and Huberman models. Results: The results of the study show that PAMI plays an important role in instilling the value of faith, getting used to worship practices, and fostering children's morals. However, its implementation faces challenges in the form of the influence of digital technology, low participation of adolescents, and limited learning methods. Implications: Revitalization of PAMI through method innovation, parental involvement, and technological adaptation can strengthen mosque-based character education. Novelty: This study highlights the revitalization of PAMI as a non-formal Islamic education model that is adaptive to the digital era and relevant to the SDGs agenda of quality education.